The Analysis of Taboo Words Translation in the Movie Death Race 2 - Aji Darma Subakti (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2017)
Taboo word usually could be found in movies, including in Death Race 2. I this research the researcher analyzed the kind of taboo words, the dialect and subtitle, quality of translation, and the impact of the kind of taboo word cases and the impacts of the casse to the quality of translation. The analysis was started by identifying the kind taboo words, continued with the quality of the text translation which is decided of the result of assessment in accuracy, acceptability, and readability by Nababan et. al. The findings of the analysis revealed that there were 75 taboo words found in the movie Death race 2 with 10 cases of kind of taboo word for its translation. Meanwhile, the quality of translation was analyzed to be; 48 were Accurate, 20 were less accurate, 7 were not accurate. 23 were acceptable, 17 were less acceptable, 35 were not acceptable. 57 were high readable, 15 were less readable, and 3 were not readable. At whole, the result of case about changed and unchanged taboo word translation in Death Race 2 movie are included into accurate, less acceptable and have high readability with the accuracy assessment is 2.68, acceptability assessment is 2.30, readability assessment is 2.79. Overall, the result of quality taboo word translation is 2.58. It means that they are less qualified translation.